Penerapan Metode Prototype Pada Perancangan Sistem Administrasi Pembayaran Karate Berbasis Website: Studi Kasus Lemkari Prabumulih - Uci Pratiwi; Khana Wijaya; Fajriyah Fajriyah (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
The development of information technology, especially the internet, is certainly welcomed by all circles, one of which has even penetrated the world of organizations. Lemkari Kota Prabumulih is a sports organization located in Prabumulih City which is engaged in the sport of karate. The system applied in several lemkari karate training locations in Prabumulih is still done manually. If a payment transaction occurs, management records the payment into a manual written ledger and only recapitulates the records in Microsoft Office Excel. So that sometimes there are often errors in recording data, errors in recording data for those who have made payments because the participants are mostly small children, the time is reduced due to slow manual data recording so that it is not effective in training due to the slow service of trainers to participants who make payments. Therefore, it is necessary to have a website-based system for every administrative service in order to facilitate the process of good data management and data transparency for trainers, participants, and participants' parents. This website was created using the PHP (Personal Hypertext Preprocessor) programming language with MySQL Database storage and using UML (Unifield Modeling Language) as a design method.